2003
DOI: 10.1016/j.jacc.2003.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent depression in circulating endothelial progenitor cells inpatients undergoing coronary artery bypass grafting

Abstract: Despite a significant increase in EPCs and release of cytochemokines during CABG, age is a major limiting factor for mobilization of EPCs. Further studies are necessary to improve the strategies for mobilization, ex vivo expansion, and re-transplantation of EPCs in aging patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
226
3
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 331 publications
(251 citation statements)
references
References 42 publications
18
226
3
3
Order By: Relevance
“…One study showed that ''EPCs,'' defined only as CD133þ/CD34þ, decreased with aging in patients with CAD scheduled for coronary bypass surgery (18). Their findings are similar to ours for PCs; however, we used a more stringent definition of EPCs that included the VEGF-R2 receptor.…”
Section: Discussionsupporting
confidence: 73%
“…One study showed that ''EPCs,'' defined only as CD133þ/CD34þ, decreased with aging in patients with CAD scheduled for coronary bypass surgery (18). Their findings are similar to ours for PCs; however, we used a more stringent definition of EPCs that included the VEGF-R2 receptor.…”
Section: Discussionsupporting
confidence: 73%
“…Deficiency in function and number of EPCs is associated with endothelial dysfunction (Scheubel et al, 2003;Heiss et al, 2005;Tao et al, 2006;Hoetzer et al, 2007). The data reported here showed that endothelial function measured by flow-mediated vasodilation in the brachial artery as well as in vitro SDF-1-induced migration and TNF-astimulated adhesion to HUVECs was markedly impaired in elderly men compared with young men, similar with prior reports (Taddei et al, 1995;Tao et al, 2004;Heiss et al, 2005;Hoetzer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…26,66,67 It has been reported that in young patients with stable coronary artery disease after coronary artery bypass grafting, the number of CEPCs increases, whereas the opposite occurs in older patients. 66 The age-related deficiency in the number of CEPCs was not related to differences in cardiovascular risk factor or cardiac function and it may be caused, at least in part, by reduced levels of angiogenic and mobilizing cytokines. This deficiency may be at the root of impaired neovascularization of ischemic tissues and attenuated re-endothelialization of injured tissues commonly observed in older patients.…”
Section: Epc and Agingmentioning
confidence: 99%
“…16,27,28,55,58,62,63 Aging and diabetes markedly reduce the availability and impair the function of EPCs. 28,[62][63][64]66,67 Because older and diabetic patients are the most vulnerable populations for cardiovascular diseases, this severely restricts the ability to treat with autologous EPCs the patients who theoretically need them most. The purity and developmental stage of the cells used for transplantation are important factors.…”
Section: Potential Problems With Therapeutic Use Of Epcsmentioning
confidence: 99%